EFFECTS PROGRAMS OF HIGH-LOW AEROBICS TO MORPHOLOGICAL CHARACTERISTICS GIRLS HIGH SCHOOL STUDENTS - Dobrislav Vujović; Rašid Hadžić; Aleksandar Vujović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The study was conducted in order to determine the value of the experimental program (high - low aerobics) and its impact on morphological characteristics in a high school student. The study was longitudinal character with one experimental and one control group. Sample is consisted of 80 students of Medical School "dr Branko Zogović" Berane which were divided into two equal groups. The experimental group that worked on the model of high - low aerobics class consisted of 40 students, while the control group consisted of 40 students who also held classes at the regular plan and program for the subject of physical education prescribed by the Ministry of Education of Montenegro. The changes that have occurred in the experimental and control student groups for a period of 12 weeks, twice a week, were followed by: morphological chara¬cte¬ris¬tics (13 measuring instruments). The results were subjected to statistical data analysis methods that included determination of descriptive statistical parameter, and for determination of statistically significant differences between the average values of the two groups at the initial and final measurements was used t-test.